PENGASASAN DAN PERANAN AGENSI PENGUATKUASAAN MARITIM MALAYSIA, 2004-2014: THE ESTABLISHMENT AND THE ROLE OF THE MALAYSIAN MARITIME ENFORCEMENT AGENCY, 2004-2014 - Mohd Rus , Ahmad Kamal Ariffin; Abdul Rahman , Zulkarnain; Mustazar , Muhammad Hidayatur Rahman (SEJARAH: Journal of the Department of History, 2021)
This article examines the Malaysian Maritime Enforcement Agency (MMEA) in the context of its establishment and role to patrol and protect the Malaysian maritime zones. The discussion focuses on its establishment, its main roles, and the challenges faced. Qualitative analysis is used to study data obtained from both primary and secondary sources. Among the primary sources used include the acts related to national maritime zones, the MMEA Annual Reports, the Malaysian International Trade and Industry Reports, Malaysian Transportation Statistics, Parliamentary Hansards, and local periodicals. Based on the sources used, the study found that the lucrative importance of our national maritime zones compelled the government to create a new specific agency to patrol and protect our waters. The MMEA operations officially began on 30 November 2005. Although this agency is responsible for national security, its staff scheme is categorised as the public sector, in contrast to the schemes of service for the Marine Police and the Malaysian Royal Navy (TLDM). The largest role and challenge of the MMEA in patrolling national waters involve both supervision and coordination. Although equipped with radar surveillance system, our vast maritime zones naturally tempt activities of piracy, smuggling, encroachments by foreign fishermen, and movements by illegal immigrants. The vague legal provisions meant other enforcement agencies are seen as operating within the ambit of MMEA portfolio, causing problems of ineffectiveness and hindering the MMEA’s role of coordination. Received: 13 February 2021 Reviewed: 5 March 2021 Accepted: 28 June 2021